1981
DOI: 10.1017/s0031182000050113
|View full text |Cite
|
Sign up to set email alerts
|

An improved technique for the cryopreservation of Onchocerca microfilariae

Abstract: SUMMARYExperiments describe the use of ethanediol to store Onchocerca microfilariae in liquid nitrogen. The technique involves a 2-stage incubation of the parasites at 37 °C and 0 °C in ethanediol, before rapid cooling to − 196 °C. Viability has been assessed by motility, by migration in a proxy host and by development to the infective stage in the insect vector. A total of 71–79% of the cryopreserved microfilariae was shown to be viable compared to unfrozen controls. The technique is simple, inexpensive and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…Ultrastructural examination by electron microscopy confirmed that these cultured larvae had started the moulting process, as the separation between the cuticle of L3 and the newly synthesized cuticle of L4 was evident in some of the cross-sections 52 . Nodular and skin microfilariae were purified as described previously 54,55 and the adult worms were excised from collagenase-treated nodules as previously described 49 . Parasites were stored in trizol until RNA isolation.…”
Section: Methodsmentioning
confidence: 99%
“…Ultrastructural examination by electron microscopy confirmed that these cultured larvae had started the moulting process, as the separation between the cuticle of L3 and the newly synthesized cuticle of L4 was evident in some of the cross-sections 52 . Nodular and skin microfilariae were purified as described previously 54,55 and the adult worms were excised from collagenase-treated nodules as previously described 49 . Parasites were stored in trizol until RNA isolation.…”
Section: Methodsmentioning
confidence: 99%
“…O. ochengi microfilariae were obtained from the ventral skin of freshly slaughtered cattle from the Adamawa province of northern Cameroon (35). The parasites were extracted from skin and cryopreserved by established procedures (3,13) and then transported to the United Kingdom in liquid nitrogen. Infective-stage larvae were produced by intrathoracic injection of microfilariae into laboratory-reared blackflies (Simulium ornatum sl.)…”
Section: Methodsmentioning
confidence: 99%
“…Microfilariae of Onchocerca lienalis were obtained from the umbilical skin of freshly killed cattle by the method of Bianco et al [2], and were cryopreserved according to the method of Ham et al [8]. Microfilariae used for intraocular infection were washed twice in Tyrode's solution containing penicillin (1,250 U/ml) and streptomycin (1.25 mg/ml) and resuspended in the same solution for injection.…”
Section: Methodsmentioning
confidence: 99%